Evaluation of confocal laser endomicroscopy as an aid to differentiate primary flat lesions of the larynx: A prospective clinical study. (28th November 2015) - Volgger, Veronika; Girschick, Susanne; Ihrler, Stephan; Englhard, Anna Sophie; Stepp, Herbert; Betz, Christian Stephan
Abstract: Background: In this trial, the ability of confocal laser endomicroscopy (CLE), a new imaging modality with a cellular resolution, to further differentiate primary flat lesions of the larynx was evaluated. Methods: First, an optical coherence tomography was used to filter out normal tissue and carcinoma. All other lesions (30 lesions in 19 patients) were investigated with CLE. The suspected diagnosis was compared to histopathology. Results: Optical coherence tomography identified all noninvasive lesions. CLE provided further information with cellular resolution. In 2 of 30 cases, low image quality prevented classification. In laryngeal lesions (27 of 30), moderate to high‐grade dysplasia was correctly suspected in 10 of 10 cases (100%). Hyperplasia was overrated as dysplasia in 7 of 15 cases (46.7%). Sensitivity was 100% and specificity was 40%. Conclusion: When used in conjunction with optical coherence tomography, CLE seems helpful for discrimination of noninvasive lesions, although it tends to overrate the severity of the changes. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1695–E1704, 2016